Comparación electromiográfica de músculos suprahioideos, masetero y orbicular de los labios en niños y niñas de 1 a 5 meses de edad, alimentados con lactancia materna o biberón (2001)
ABSTRACT: A non probabilistic sample of 20 children between 1 and 5 months of age was selected, 10 children were breast fed and 10 bottle fed to which electromyography with surface electrodes was performed on the supra hyoid muscles, masseter and orbicularis oris. For each muscle, 20 action potentials were selected, which meant a total of 200 action potentials per muscle in each group. It was found that the highest muscle activity in both groups was in the supra hyoids, followed by the orbicularis oris and the last the masseter. There were statically significant differences between the activity of the supra hyoids and orbicularis oris, but not with the masseter. The highest activity of the supra hyoid muscles was found in the breast fed group, and the highest activity of the orbicularis oris was in the bottle fed group.